The Pan-Deacetylase Inhibitor Panobinostat Inhibits Growth of Hepatocellular Carcinoma Models by Alternative Pathways of Apoptosis - Pietro Di Fazio; Regine Schneider-Stock; Daniel Neureiter; Kinya Okamoto; Till Wissniowski; Susanne Gahr; Karl Quint; Matthias Meissnitzer; Beate Alinger; Roberta Montalbano; Gabriele Sass; Bernd Hohenstein; et al. (Cellular Oncology)
Inhibition of deacetylases represents a new treatment option for human cancer diseases. We applied the novel and potent pan-deacetylase inhibitor panobinostat (LBH589) to human hepatocellular carcinoma models and investigated by which pathways tumor cell survival is influenced.